Juridical Review of the Balance of Position of the Parties in the Micro Business Credit Agreement - Dhenandra Mahardika Sukmana (IHSA Institute, 2020)
Loans granted by banks need to be secured, without the presence of bank safeguards it is difficult to evade from arising as a result of debtor underachievement. Therefore banks bind debtors in micro business credit agreements based on the legal relationship between banks and credit. This research is to find out how micro business credit agreements have a balanced position for the parties. The method uses normative juridical research and the method used uses licensing (statute-approach) and analytical (analytic approach). The results obtained from this study are expected to provide a clear description and detailed, systematic and thorough legal review of the equilibrium position of the parties to the micro credit agreement.